2021
DOI: 10.1073/pnas.2103027118
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota-derived metabolites inhibit Salmonella virulent subpopulation development by acting on single-cell behaviors

Abstract: Salmonella spp. express Salmonella pathogenicity island 1 Type III Secretion System 1 (T3SS-1) genes to mediate the initial phase of interaction with their host. Prior studies indicate short-chain fatty acids, microbial metabolites at high concentrations in the gastrointestinal tract, limit population-level T3SS-1 gene expression. However, only a subset of Salmonella cells in a population express these genes, suggesting short-chain fatty acids could decrease T3SS-1 population-level expression by acting on per-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Genes involved in several metabolic pathways were enriched in S. Tm from superspreader mice compared to in vitro samples (Figure 2B). Genes that encode known virulence factors, such as ssaV, sifA, pipB2, and sseI, were expressed at lower levels in the gut compared to in vitro growth conditions, which is consistent with the expression of these virulence factors being important for S. Tm growth and survival in tissues rather than growth in the gut lumen (Diard et al, 2013;Hockenberry et al, 2021). In contrast, genes previously demonstrated to impact Salmonella colonization of the gut, such as fucose metabolism (fucA, fucO, fucK) (Deatherage Kaiser et al, 2013;Ng et al, 2013) and fimbriae genes (stdA, stdB) (Chessa et al, 2008;Suwandi et al, 2019) were expressed at higher levels in the guts compared to in vitro growth conditions (Figure 2B).…”
Section: S Tm Gene Expression In Guts Of Superspreader Micesupporting
confidence: 63%
“…Genes involved in several metabolic pathways were enriched in S. Tm from superspreader mice compared to in vitro samples (Figure 2B). Genes that encode known virulence factors, such as ssaV, sifA, pipB2, and sseI, were expressed at lower levels in the gut compared to in vitro growth conditions, which is consistent with the expression of these virulence factors being important for S. Tm growth and survival in tissues rather than growth in the gut lumen (Diard et al, 2013;Hockenberry et al, 2021). In contrast, genes previously demonstrated to impact Salmonella colonization of the gut, such as fucose metabolism (fucA, fucO, fucK) (Deatherage Kaiser et al, 2013;Ng et al, 2013) and fimbriae genes (stdA, stdB) (Chessa et al, 2008;Suwandi et al, 2019) were expressed at higher levels in the guts compared to in vitro growth conditions (Figure 2B).…”
Section: S Tm Gene Expression In Guts Of Superspreader Micesupporting
confidence: 63%
“…Nonetheless, recent molecular studies in combination with bacterial genetics and in vivo infection models have demonstrated the contributions of LCFAs in regulating the virulence potentials of bacterial pathogens in the gut. Finally, it should be noted that short chain fatty acids (SCFAs)nonesterified fatty acids with fewer than six carbonsare even more abundant within the gut and can also act as signaling molecules that modulate virulence through diverse mechanisms (Cummings et al, 1987;Lawhon et al, 2002;Gantois et al, 2006;Hung et al, 2013;Zhang et al, 2020;Hockenberry et al, 2021;Hobbs et al, 2021), recently reviewed here (Mirzaei et al, 2021).…”
Section: Long Chain Fatty Acidsmentioning
confidence: 99%
“…To accomplish this feat, pathogens deploy a suite of virulence factors including pili, toxins, and type III secretion systems to establish a replicative niche, which disrupts homeostatic intestinal functions and can result in disease. Despite their necessity for pathogen colonization, many virulence factors are energetically costly to produce (Sturm et al, 2011;Diard et al, 2013;Vasanthakrishnan et al, 2015;Davis, 2020;Hockenberry et al, 2021). Consequently, the expression of virulence genes is tightly regulated by transcription factors and complex signaling networks that link pathogen sensing of the environment to optimal activation of their virulence programs (Pacheco and Sperandio, 2015;Nisco et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Considering that firstline antibiotic treatment disrupts the normal gut microbiome, resulting in the loss of SCFA-dependent induction of pyroptosis that may be helpful in clearing infection, improved understanding of the normal gut microbiome and its role during pyroptosis holds therapeutic promise for treatment of Salmonella. SCFAs have been described to suppress the growth of T3SS-expressing bacteria (Hockenberry et al, 2021) and, therefore, it is still unclear whether the effect of SCFAs on pyroptosis is direct, i.e. acting on the host cell, or indirect, i.e.…”
Section: Activation Of Pyroptosis By Salmonellamentioning
confidence: 99%